Rancang Bangun Monitoring Solar Home System Berbasis Internet of Thing Pada Komplek Peternakan Kambing PE Marsudi Luhur - Anna Nur Nazilah Chamim; Ramadoni Syahputra; Ryan Permana Putra (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
The PE Goat Farm Complex, with an area of about 600 m2 located in Mertosutan Hamlet, Sidoluhur Village, Godean District, Sleman Regency, Yogyakarta Special Region Province, has a lighting system from a hybrid solar home panel system with solar panels as the main source and PLN as a backup source. The system for switching resources from solar panels to PLN sources or vice versa is carried out automatically with an ATS (Automatic Transfer Switch) circuit so that no human resources are needed for its operations. The performance of the solar home system is the most important element in the supply system, so it needs to be monitored regularly. This program aims to design a solar home system performance monitoring system based on the Internet of Things (IoT). The method applied in this program is Design Improvement. The design of the system is made by adding a series of electrical components that are applied to the solar home system at the location. The power, current, voltage, and light intensity generated by the solar home system are sent to the application via the internet in real-time. The results of testing the implementation of an IoT-based monitoring system design can work optimally with a 100% success rate. The implication is that the use of a solar home system at the Marsudi Luhur Goat Farm Complex can be maintained for stability and sustainable performance through an IoT-based monitoring system that has been implemented.